Impact of breast cancer and quality of life of women survivors - Julia Viana Lopes; Cristiane Decat Bergerot; Luciene Rodrigues Barbosa; Nilciza Maria de Carvalho Tavares Calux; Simone Elias; Kimlin Tam Ashing; Edvane Birelo Lopes de Domenico
ABSTRACT Objective: To evaluate the impact of breast cancer and the quality of life of women survivors and to identify associations between sociodemographic and clinical variables. Method: This was a cross-sectional, analytical, quantitative study conducted with women receiving outpatient post-treatment care at a public institution of the city of São Paulo, state of São Paulo, Brazil. Instruments: sociodemographic and clinical questionnaires; Impact of Cancer scale; Functional Assessment of Cancer Therapy-Breast Cancer scale. Descriptive and analytical statistical analysis were performed. Results: One hundred women were included in the study with a mean age of 60 years (SD = 11.3); most with less than 5 years of follow-up, low purchasing power, and low education levels. Negative Impact of Cancer: Health Worry, Body Changes, Feelings, and Meaning of Cancer. Quality of life: 81.9 (18.3), specific: 105.6 (24.6). The following subscales of the impact of cancer scale predicted lower quality of life scores: Body Changes, Negative Self-Evaluation, and Concerns about Cancer (p <0.05). Conclusion: Although they presented high scores for quality of life, patients reported negative impacts of cancer, enhanced by vulnerabilities.